The influence of corporate governance on financial performance in the hospitality industry - Lim, Zi Wei (2023)
The performance and stability of the hotel sector have suffered because of COVID-19's widespread distribution. Mechanisms for corporate governance (CG) are essential for guaranteeing regulatory compliance, fostering stakeholder responsibility, and lowering risk in the hospitality industry. This study aims to look at how CG may have affected the financial results of the listed hospitality firms between 2018 and 2021. 66 publicly traded hospitality organisations from across the world have been chosen as the subject of this research project. Earnings per share (EPS) and return on assets (ROA) are used to measure a company's success in terms of finances. The following CG practises practices are examined in this study: diligence, board size, board makeup, board meetings, and environmental and social disclosures. On the other side, the research study's control variable will be the size of the firm. This research is going to use the correlation matrix, the multicollinearity test, the multiple regression analysis, and T-test analysis. The results of each of the factors have been considered while interpreting and discussing the analysis. According to the data, the CG mechanism that has a substantial beneficial influence on company performance is the proportion of independent board members and the size of board. Also, following the COVID-19, environment pillar score appeared to be considerably improving the company performance (the years 2020 and 2021).Hence, it can be inferred from the study that while not all CG measures may significantly affect financial performance, some of them may have positive or negative effects on the financial performance of listed hospitality organisations. Finally, this study on the effects of CG and COVID-19 on financial performance can offer operators and directors in the hotel sector with useful information that will help them make decisions that will boost business success and stakeholder confidence.